Sistem Notifikasi Penjadwalan Perawatan Kendaraan Berbasis Web dengan WhatsApp Gateway di PT Indokarya Teknik - Anisa, Efi (Jurnal Ilmiah Informatika Global, 2025)
PT Indokarya Teknik is a company that operates numerous vehicles requiring regular maintenance to ensure optimal performance. However, the manual scheduling system currently in place often leads to delays, negligence, and inefficiencies in vehicle maintenance management. Therefore, this study aims to design and develop a Web-Based Vehicle Maintenance Scheduling Notification System with WhatsApp Gateway to automate maintenance schedule reminders for users or relevant technicians. The development of this system follows the Waterfall Model, which includes requirement analysis, system design, implementation, testing, and maintenance. The system is built using web-based technology with the Laravel framework and is integrated with a WhatsApp Gateway to send automated notifications to users. System testing is conducted using the Black Box Testing method to ensure that all features function according to the specified design. The results indicate that this system enhances efficiency in managing vehicle maintenance schedules, reduces the risk of missed schedules, and facilitates communication between the company and technicians through real-time notifications. With this system, PT Indokarya Teknik is expected to optimize its vehicle maintenance operations, thereby improving overall operational effectiveness and efficiency.